Social equality in Indian society: the elusive goal - Augustine, P.A. (New Delhi Concept publishing, 1991)
Time was when social equality was an unmentionable topic in the higher strata of Indian Society. Yet, by an incredible twist of history, the principle of social equality found its place at the very heart of the constitution of Independent India. History has few parallels to such a transformation. The change was not wrought by a brief tempestuous revolution but was the outcome of a millennia-long struggle. This struggle forms the theme of the present book. The unfolding saga brings clearly before out eyes the many vicissitudes of the movement toward social equality. A galaxy of inspired men and women stride across the arena of history. Among them are philosophers and founders of religious sects, poets and ascetics, visionaries and social activists. A common vision unites them all. They dream of an age when social barriers are no more, when no one is penalized for the circumstances of one???s birth, when no one is despised on account of the colour of one???s skin. This vision is nurtured by their unshakable faith in the dignity and equality of all men and women. The narrative guides the reader from the dim pre-historical past, through the historical times marked by vitality stagnation, turbulence and trauma into the 20th Century to the down of India???s independence, the birth of the Constitution and its aftermath. The book succeeds in capturing the drama, the tensions and the conflict of interests in the blossoming of a grand vision. And the tale is eloquently told here, with sensitivity and perspicacity, by a gifted freelance journalist.
Keywords: Sociology